Survey of the Current Status and Seasonal Problems Associated with Rabbit Production in Kaduna Metropolis (Journal of Basic and Applied Research in Biomedicine, 2022)
A survey was carried out to ascertain the current status and seasonal problems associated with rabbit production in Kaduna metropolis. Two hundred structured questionnaires were distributed to respondents within the ten study areas as follows: Barnawa, Kurmin-mashi, Kakuri, Kawo,Uguwan,Dosa, Mando, Unguwa-romi, Tudun-wada, Sabon-gari Zaria and Shika Zaria.The following information were sort for from the rabbit farmers: how long they have been involved in rabbits keeping, the type of breeds of rabbits kept, the maximum and minimum number of rabbits ever kept, the reasons for the choice of feeds, availability of the feeds during dry and raining season, problems faced in feeding the rabbits during dry season, common diseases during the two seasons and the advantage of keeping rabbits over other micro livestock. All the data obtained were analyzed using simple frequency distributions. Results shows that there were more male keeping rabbits than female 63.3% and 36.7% respectively. People within the age group of 21-30 years are more into rabbit farming than all other age group. There were more civil servants keeping rabbits than all other profession. 59.20% of the respondents preferred keeping rabbits during wet season when compared to the 40.80% that preferred dry season. Some of the difficulties experienced by farmers include: scarcity of greens/vegetables during dry season, high cost of feed, lack of good storage facilities for hay which does not last throughout the period of scarcity, diseases such as diarrhea and bloat. Possible ways of reducing and controlling these problems were suggested.